A Blended Learning Method Applied in Data Communication and Computer Networks Subject - N Leite, Frederico; Shigueo Hoji, Eduardo; Abdalla Junior, Humberto (Revista IEEE América Latina, 2018)
Traditional lectures are not effective for teaching practical subjects. So, it's important to develop a methodology capable to provide to the students the conceptual and practical aspects of a course. In this paper, we describe the challenges faced in the implementation of active learning methods in the subject of Data Communication & Computer Network in vocational education at the Federal Institute of Brasília. The experiences resulted in a blended methodology which combines collaborative and problem-based learning with a learning management system. The flipped classroom was also applied in order to enhance the quality of the references used by the students in the solutions. Also, traditional apps and social networks were used to enhance the communication between students and professor. The results of the comparative study show that the students' performance and the quality of the developed activities in the subject were improved under active learning in comparison to Traditional Lectures. Moreover, transversal skills, such as, teamwork, leadership, self-confidence and autonomy in decision-making could be developed. The research was started in 2011 to 2016 and 162 students were enrolled. Such features demonstrate the learning methodology must be fit to the course and the educational level in order to became effective.